Prospek dan Etika Penggunaan Learning Analytics (Analisis Data Pembelajaran) untuk Meningkatkan Kualitas Pengajaran - Saputra, Wahyu; Akmila, Anggun (Universitas Islam Tribakti Lirboyo Kediri, 2025)
The development of information and communication technology has brought significant changes to the field of education, particularly through the utilization of learning data. Learning analytics has become one of the strategic approaches used to understand learners’ learning behaviors and to improve the quality of teaching. This article aims to examine in depth the prospects of implementing learning analytics in educational contexts and to analyze the ethical issues that arise from its application. The research method employed in this study is library research, which involves reviewing various relevant journals, books, and scientific reports. The results of the analysis indicate that learning analytics has great potential in supporting personalized learning, enhancing teaching effectiveness, predicting academic performance, and facilitating data-driven pedagogical decision-making. However, the implementation of learning analytics also presents significant ethical challenges, including issues related to data privacy, information security, transparency in data use, algorithmic bias, and fairness in the treatment of learners. Therefore, ethical frameworks, regulatory policies, and collective awareness are necessary to ensure that learning analytics is implemented in a responsible and sustainable manner.